Incidence of and Causes for Ventriculoperitoneal Shunt Failure in Children Younger Than 2 Years: A Systematic Review - Hasanain, Amr Ali; Abdullah, Ahmed; Alsawy, Mohamed F. M.; Soliman, Mohamed A. R.; Ghaleb, Ammar Ali; Elwy, Reem; Ezzat, Ahmed A. M.; Al Menabbawy, Ahmed; Marei, Ahmed A.; Abd el Razik, Bassante; El Hamaky, Mostafa I.; Schroeder, Henry W. S.; Fleck, Steffen; El Damaty, Ahmed; Marx, Sascha; Nowak, Stephan; Baldauf, Jörg; Zohdi, Ahmed; El Refaee, Ehab Ahmed (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Objectives Ventriculoperitoneal (VP) shunting is commonly used to treat pediatric hydrocephalus, but failure rates are high. VP shunt failure in children is mostly caused by infection and/or proximal/distal shunt obstruction. However, to our knowledge, no previous reviews have discussed this topic using only clinical studies when age-related data could be obtained. This systematic review aimed at reevaluating what is already known as the most common causes of shunt failure and to determine the incidence and causes of VP shunt failure during the first 2 years of life as a step to establish solid evidence-based guidelines to avoid VP shunt failure in infants.Methods We performed a search using the search terms “Cerebrospinal Fluid Shunts” (Medical Subject Headings [MeSH]) AND failure [All Fields] AND (“humans” [MeSH] AND English [lang] AND “infant” [MeSH]). Only articles that specifically discussed VP shunt complications in children < 2 years were included.Results We found that the most common causes of VP shunt failure in children < 2 years were shunt obstruction and infection, both observed in a range.Conclusion VP shunt failure is very common in infants, mostly resulting from obstruction and infection. Future studies should focus on methods designed to avoid these complications or on alternative treatments for hydrocephalus.
Keywords: failure; infants; infection; obstruction; ventriculoperitoneal shunt